CSR INITIATIVES AND SUSTAINABILITY RESILIENCE IN NIGERIA'S OIL AND GAS INDUSTRY: A PLS-SEM APPROACH FROM LOCAL COMMUNITIES' PERSPECTIVE - Tajudeen Alaburo Abdulsalam; Rofiat Bolanle Tajudeen; Abdulrahman Abubakar; Akeem Olamilekan Babatunde (Gusau Journal of Accounting and Finance)
Despite its potential for economic growth and sustainable development, Nigeria faces social challenges including poverty, environmental degradation, and economic decline. In 2023, it ranked 146th out of 166 on the SDG index, with a poverty headcount of $2.15/day. Over the past two decades, Nigerian oil and gas companies have faced sustainability criticism, emphasizing the importance of CSR initiatives for triple bottom line sustainability. This study examines how the CSR initiatives of Nigerian energy companies impact the sustainability and resilience of the Niger Delta region. By using an explorative research design guided by positivism philosophy, 460 survey responses were collected from Niger Delta community members via Google Form and analyzed using PLS-SEM since the research framework of the CSR and COM-R model comprises five primary dimensions each. The study discovered that CSR initiatives have a significant impact on sustainability and resilience in the Niger Delta. This underscores that integrating socially responsible initiatives not only enhances the ethical standing of these businesses but also generates high strategic value, bolstering their sustainability and resilience. The research recommendations include reassessing CSR initiatives, increasing community engagement, and collaborating with regulatory bodies. This will foster community cohesion, adaptability, and voluntary compliance with industry standards and social norms within the community. The research's descriptive value lies in its empirical demonstration of the connection between CSR and sustainability resilience. Firms can use these findings to enhance their CSR efforts and improve sustainability and resilience in future business practices. The research acknowledges potential biases in data collection stemming from unequal online access among the members of Niger Delta communities, resulting in a partial representation of the diverse range of respondent behaviours across the continent, as various cultural, economic, and social factors can influence their survey responses.